Assessment of the rules related to gaining activity against Gram-negative bacteria. Issue 4 (3rd March 2021) - Ropponen, Henni-Karoliina; Diamanti, Eleonora; Siemens, Alexandra; Illarionov, Boris; Haupenthal, Jörg; Fischer, Markus; Rottmann, Matthias; Witschel, Matthias; Hirsch, Anna K. H.
Abstract : Evaluation of the applicability of Gram-negative activity rules using 16 amino acid modified compounds against a panel of Escherichia coli and its mutant strains. Abstract : In the search for new antibacterial compounds, we repositioned an antimalarial compound class by derivatising it based on the so-called "eNTRy" rules for enhanced accumulation into Gram-negative bacteria. We designed, synthesised and evaluated a small library of amino acid modified compounds together with the respective Boc-protected analogues, leading to no substantial improvement in antibacterial activity against Escherichia coli wild-type K12, whereas more distinct activity differences were observed in E. coli mutant strains Δ tolC, D22, Δ acrB and BL21(DE3)omp8. A comparison of the activity results of the E. coli mutants with respect to the known rules related to enhanced activity against Gram-negative bacteria revealed that applicability of the rules is not always ensured. Out of the four amino acids used in this study, glycine derivatives showed highest antibacterial activity, although still suffering from efflux issues.